Design methodology for general enhancement of a single-stage self-compensated folded-cascode operational transconductance amplifiers in 65 nm CMOS process - Hayder Khaleel AL-Qaysi; Adham Hadi Saleh; Tahreer Mahmood (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The problems resulting from the use of nano-MOSFETs in the design of operational trans-conductance amplifiers (OTAs) lead to an urgent need for new design techniques to produce high-performance metrics OTAs suitable for very high-frequency applications. In this paper, the enhancement techniques and design equations for the proposed single-stage folded-cascode operational trans-conductance amplifiers (FCOTA) are presented for the enhancement of its various performance metrics. The proposed single-stage FCOTA adopts the folded-cascode (FC) current sources with cascode current mirrors (CCMs) load. Using 65 nm complementary metal-oxide semiconductor (CMOS) process from predictive technology model (PTM), the HSPICE2019-based simulation results show that the designed single-stage FCOTA can achieve a high open-loop differential-mode DC voltage gain of 65.64 dB, very high unity-gain bandwidth of 263 MHz, very high stability with phase-margin of 73°, low power dissipation of 0.97 mW, very low DC input-offset voltage of 0.14 uV, high swing-output voltages from −0.97 to 0.91 V, very low equivalent input-referred noise of 15.8 nV/Hz, very high common-mode rejection ratio of 190.64 dB, very high positive/negative slew-rates of 157.5/58.3 V⁄us, very fast settling-time of 5.1 ns, high extension input common-mode range voltages from −0.44to 1 V, and high positive/negative power-supply rejection ratios of 75.5/68.8 dB. The values of the small/large-signal figures-of-merits (????????????s) are the highest when compared to other reported FCOTAs in the literature.